A spotted landscape: Threats to leopard, Panthera pardus pardus, & their prey within the Boland Mountain Complex, Western Cape - Schultz, Brittany Claudia (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.